The Influence of Digital Learning Media on the Learning Motivation of Students at Bumrungsuksa Islamic Boarding School, Thailand - Hasrian Rudi Setiawan; Rindi Irma Audia (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the influence of digital learning media on the learning motivation of students at Bumrungsuksa Islamic Boarding School, Thailand. The research employs a Mixed Method Research approach to comprehensively gather quantitative and qualitative data. Research instruments include questionnaires to measure learning motivation levels and in-depth interviews with students and teachers to explore their experiences and perceptions. The results indicate that the use of digital learning media significantly enhances students' learning motivation, particularly in terms of interest and active participation. However, challenges such as limited access to technological devices and infrastructure support were also identified. This study recommends improving digital facilities and providing teacher training to maximize the benefits of digital learning media in educational environments.